Use of residual strips of timber by moose within clearcuts in Northwestern Ontario - Mastenbrook, Brian G. (1991)
Leaving strips of uncut timber within clearcuts has been questioned as an effective option for moose (Alces alces) management. Winter use of strips of timber was examined in six study sites in Northwestern Ontario. Winter aerial track surveys and spring browse surveys in 1987 and 1988 showed that moose used areas near the strips of residual timber within clearcuts during the winter. The area within 45 m of the strips was preferred (p<0.05) in 2 of 11 cases and used as available in the remaining 9 cases. The area within 90 m of the strips was preferred in 5 of 11 cases and used as available in the other 6 cases. Aerial track survey data also showed that moose significantly (p<0.01) preferred the area within 45 and 90 m of cover. Analysis of spring browse survey data showed no significant (p<0.01) difference between the number of stems available or browsed that was related to distance from the strips. Significant (p<0.01) differences between the number of twigs available and browsed were found but differences in browsing seemed related to availability rather than increasing distance from the strips. Snow surveys showed significantly (p<0.01) lower snow depths within the strips than in the cutover. Snow depth and conditions adjacent to the corridor may have been influenced by the strips, but were also influenced by wind, terrain and ground cover. Residual strips of timber were not being used specifically for feeding areas but may have been used as escape cover, thermal cover or as travelling areas.